Dynamics of solar radiation and soybean yield in agroforestry systems - CARON,BRAULIO O. (2018)
Abstract Soybean (Glycine max L.) monocropping have had a great socio-economic and environmental impact on the world and agroforestry systems has been considered an alternative for more sustainable production. The aim of this study was to evaluate the effect of different arrangements of agroforestry systems of the species E. urophylla x E. grandis and P. dubium and the pruning of the trees on the dynamics of solar radiation and soybean yield. A field experiment was conducted in Southern Brazil. In order to achieve the objective of the study, the solar radiation transmissivity and the productive performance of the soybean were evaluated. In this study, the soybean yield was determined by the arrangement of the agroforestry system and forest species utilized. The soybean crop cultivated in the understory of the P. dubium trees showed the highest yield response. The use of silvicultural practices for the management of forest species should be considered to generate the balance of the productive system. In this context, tree pruning is a viable side for agroforestry systems, as it promotes an increase in the incidence of solar radiation in the understory, resulting in an increase in soybean yield, especially when integrated with P. dubium.